Customer Perception of Banking Services in Islamic Banks: A Literature Review and Social Media Analysis of Bank Syariah Indonesia (BSI) - Saifullah, T; Alfikri, Albert (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The consolidation of three state-owned Islamic banks in Indonesia into Bank Syariah Indonesia (BSI) in 2021 marked a significant development in the Islamic banking sector. As the largest Islamic bank in Indonesia, BSI is expected to offer superior service quality while maintaining adherence to Sharia principles. This paper presents a comprehensive literature review of international studies on customer perception and service quality in Islamic banking, with a particular focus on digital banking, customer satisfaction, and loyalty. Additionally, this study incorporates a critical social media analysis to understand public opinion on BSI’s service delivery. The findings indicate that while BSI’s digital services have been positively received, challenges persist in customer service responsiveness, transparency, and application reliability. Social media sentiment often amplifies these challenges, highlighting the need for proactive management and strategic communication. The synthesis of literature and social media insights provides actionable recommendations for enhancing service quality and customer satisfaction in Islamic banking.